Island livelihoods: Tourism and fishing at Long Islands, Shandong Province, China. (March 2016) - Su, Ming Ming; Wall, Geoffrey; Jin, Min
Abstract: Tourism may enhance island livelihood options, reduce fishing pressures but place new demands on limited resources and disrupt local livelihood systems and socio-cultural traditions. Two fishing villages at Long Islands in Shandong Province, China, are compared using a sustainable livelihood framework to assess livelihood changes induced by Yujiale tourism, a special type of coastal tourism. It is found that livelihoods are enhanced at the community level through the incorporation of Yujiale tourism which uses existing resources of fishing and mariculture and generates jobs and income to supplement these traditional livelihoods. However, an unequal distribution of tourism benefits was found where the poor were largely excluded due to financial limitations. A comparison of the two cases suggests that local leadership affects Yujiale tourism development and its impacts on traditional livelihoods. Practical implications are discussed at both community and household levels to enhance livelihoods sustainability for island communities. Highlights: We analyze Yujiale tourism in two fishing villages at Long Islands in China. SLF is used to assess and compare tourism induced livelihood changes. Relations between fishing and Yujiale tourism as livelihood options are discussed. Local leadership is found to affect Yujiale tourism and its impacts on livelihoods. Practical implications are discussed to enhance island livelihood sustainability.